Runtime recovery actions selection for sporadic operations on public cloud. (15th July 2016) - Fu, Min; Zhu, Liming; Sun, Daniel; Liu, Anna; Bass, Len; Lu, Qinghua
Summary: Sporadic operations such as rolling upgrade or machine instance redeployment are prone to unpredictable failures in the public cloud largely because of the inherent high variability nature of public cloud. Previous dependability research has established several recovery methods for cloud failures. In this paper, we first propose eight recovery patterns for sporadic operations on public cloud. We then present the filtering process which filters applicable recovery patterns. We propose an automation mechanism to automatically generate recovery actions for those applicable recovery patterns based on our resource state transition algorithm. We also propose a methodology to evaluate the recovery actions generated for the applicable recovery patterns based on the recovery evaluation metrics of Recovery Time, Recovery Cost, and Recovery Impact. This quantitative evaluation will lead to selection of the acceptable recovery actions. We propose two recovery actions selection mechanisms: one is based on user constraints of the recovery evaluation metrics, and the other one is based on Pareto set searching algorithm. We implement a recovery service and illustrate its applicability by recovering from errors occurring in the rolling upgrade operation on AWS cloud.